Whytockia (Gesneriaceae), a new generic record for India, based on a new species, W. arunachalensis, from Arunachal Pradesh, India - Taram , M.; Borah , D.; Tag , H.; Möller, M.; Weber, A. (Rheedea, 2026)
Based on recent collections from Arunachal Pradesh (Northeast India), a new species of Gesneriaceae, Whytockia arunachalensis, Taram, D. Borah & Tag is described. It differs from the other species of Whytockia W.W.S.m. by its extensive, dense and uniform indumentum over the entire plant and is closely related to the white, but smaller-flowered congeners W. tsiangiana (Hand.-Mazz.) A. Weber and W. sasakii (Hayata) B.L. Burtt. Up to now, Whytockia was only known from South and Central China and Taiwan and this is the first record of the genus for India. For that reason, some general information (including a key to the genus and genus description) and critical notes on the species and characters of Whytockia are provided.